What Women Want: Mental Health in the Context of Violence Against Women in Sri Lanka—A Qualitative Study of Priorities and Capacities for Care - Palfreyman, Alexis (Violence against women, 2025)
Insufficient evidence guides mental health service development for survivors of violence against women in Sri Lanka. Provider and survivor perspectives on (1) what constitutes mental health, (2) quality of care, and (3) priority areas and stakeholders for intervention were identified through framework analysis of 53 in-depth interviews. Desired care is chiefly psychosocial—not psychological—prioritizing socioeconomic, parenting, and safe environment needs in non-clinical community settings. Our evidence points strongly to the need to strengthen non-mental health community-based providers as “first contacts” and reassessment of health system-centric interventions which neglect preferred community responses and more holistic approaches accounting for women's full circumstances.